Architectural configuration of a magnetic flux density amplifier composed of second-generation high-temperature superconducting (2G HTS) 8-shaped rare earth-Ba–Cu–O (REBCO) loops. Issue 2 (4th March 2022) - Wang, Jiawen; Wang, Yinshun; Wang, Jian; Zhang, Guangyi; Liu, Wei; Pi, Wei
Abstract: Superconducting devices composed of the second-generation high-temperature superconducting (2 G HTS) RE-Ba-Cu-O (REBCO, RE is rare earth) tapes have extensive applications in high magnetic flux density measurements. Here an architectural configuration for a magnetic flux density amplifier is designed and an experimental setup is established to characterize the amplification of the magnetic flux density. The system is composed of REBCO HTS tapes with one central slit excited by field cooling. The HTS tape has a longitudinally cut slit with a width of 12 mm that is transversally pulled apart and mechanically twisted to form an 8-shaped loop with two different sized closed-loops. The large closed-loop includes an excitation coil composed of copper wire wound on an iron core so that there is more dense flux density generated in the smaller closed-loop. The amplified magnetic flux densities in the small closed-loops have been verified experimentally and by simulation at 77 K. The results demonstrate that the REBCO loops amplify the magnetic flux density.